(untitled) - Reed, Peter (Australia, 2007)
Strategic marketing planning provides a step-by-step guide to each stage of the marketing plan and strategy development process. Featuring a practical and concise approach, this text is an invaluable resource for students and business practitioners charged with the responsibility of developing a strategic marketing plan.
Keywords: Marketing,Marketing,Tiếp thị,Tiếp thị; Management,Decision making,Quản lý,Ra quyết định